Globalization of tobacco marketing, research and industry influence: perspectives, trends and impacts on human welfare - Yach, Derek; Bettcher, Douglas (1999)
Derek Yach and Douglas Bettcher examine how the globalization of tobacco marketing, trade, research and industry influence is a major threat to public health worldwide. They show how the tobacco industry operates as a global force buying influence and power in order to penetrate markets across the world. They propose ways to strengthen tobacco control's fight back based on utilizing the new communication technologies for effective partnerships for global regulation. - Reproduced
Keywords: Health services; Globalization; Tobacco